Mycobacterium avium subspecies paratuberculosis (MAP) becomes a public health concern in developed countries which associated with Crohn’s disease (CD) in human and Johne’s disease (JD) in ruminants. Some researchers in Europe, USA, and Australia detected MAP in the dairy products and showed the relationship among MAP, CD, and JD. Meanwhile Indonesia imported milk and milk products from those countries to cover national demand. In the future it will be a potential problem to national dairy he - Widagdo Sri Nugroho; Mirnawati Sudarwanto; Denny Widaya Lukman; Surachmi Setyaningsih; Rochman Naim; Ewald Usleber (Forum Pasca Sarjana, 2009)
Mycobacterium avium subspecies paratuberculosis (MAP) becomes a public health concern in developed countries which associated with Crohn’s disease (CD) in human and Johne’s disease (JD) in ruminants. Some researchers in Europe, USA, and Australia detected MAP in the dairy products and showed the relationship among MAP, CD, and JD. Meanwhile Indonesia imported milk and milk products from those countries to cover national demand. In the future it will be a potential problem to national dairy herd and human health. The aim of this study is to detect MAP in the growing up milk formula. Fifty samples from five established distributors were taken in Bogor. Some diagnostic methods were used parallel in this study, namely Mycobacterial Growth Indicator Tube (MGIT), Herrold’s Egg Yolk enrichment with mycobactine-J (HEYM) and polymerase chain reaction method (PCR) with insertion sequence IS 900 and F 57 as primer. Neither MAP grew up in MGIT and HEYM after 20 weeks of incubation period. No positive samples were found by conventional PCR using IS 900 and F57 either but 5 samples were detected positive by nested PCR F57. Although there was no evidence of MAP grew from the samples in this study, the comprehensive and sustainable studies on MAP still should be carried out with more and varied samples, as well as in human to provide data on MAP and to anticipate it in Indonesia. Key words: mycobacterium avium subspecies paratuberculosis, growing up milk formula, PCR